Disabled Cyclists and the Deficit Model of Disability - Inckle, Kay (Disability Studies Quarterly, 2019)
Disability and cycling rarely appear in the same sentence and there is very little research about cyclists with physical disabilities. Nor, indeed, is there any acknowledgement of the experiences and needs of disabled cyclists in policy, practice or the public imagination. Nonetheless, cycling is a key form of mobility for people with disabilities, and cycling facilitates autonomy and independence of movement for many disabled people, as well as providing health-promoting physical activity. Drawing from qualitative interviews, this paper explores this gap in the context of the deficit model of disability and its impacts upon people with physical disabilities who cycle, many of whom who use their cycle as their main form of transport and mobility. It highlights the barriers that disabled cyclists face in terms of mobility, accessing cycling and the perceptions and attitudes which impede their everyday activities and underpin exclusionary policy, practice and infrastructure. Rejecting the deficit model of disability and recognising cycling as a key strength/ability for people with physical disabilities will lead to greater equality and improve the lives and experiences of disabled people.